Local anaesthetic drugs. Issue 2 (February 2020) - Perrin, Sarah L.; Bull, Christopher; Black, Sheila
Abstract: Local anaesthetics (LA) are weak bases consisting of a lipophilic aromatic ring linked to a hydrophilic tertiary amine by either an ester or amide bond. It is this chemical link that enables classification of the LA. They exist in solution as an equilibrium of ionized and unionized forms. The unionized form is free to diffuse across the axonal membrane, but it is the ionized form which then binds and blocks the intracellular portion of the voltage gated sodium channel, preventing sodium influx and nerve transmission. Neuronal activity and nerve fibre diameter determine neuronal sensitivity; whereas pKa, lipid solubility, protein binding and inherent vasomotor activity affect the pharmacological properties of the LA. LAs can be administered by a variety of methods depending on clinical requirement including topical, local infiltration, intravenous and neuraxial and peripheral nerve blockade. While generally safe, the toxic effects of LAs can have wide-ranging effects including methaemoglobinaemia and systemic toxicity. The effects of ion trapping, stereoisomers, and additives have significant clinical consequences and require special consideration.